Anaplastic lymphoma kinase‐positive anaplastic large cell lymphoma: current and future perspectives in adult and paediatric disease. (21st May 2014) - Eyre, Toby A.; Khan, Dalia; Hall, Georgina W.; Collins, Graham P.
Abstract Anaplastic large cell lymphoma (ALCL) is a rare T‐cell lymphoma seen in both adults and children. ALCL is associated with a characteristic chromosomal translocation, t(2;5)(p23;35) which fuses the anaplastic lymphoma kinase (ALK) gene on chromosome 2 with the nucleophosmin (NPM) gene on chromosome 5, resulting in a NPM‐ALK fusion protein, ALK over‐expression and constitutive tyrosine kinase activity. This aggressive lymphoma is more prevalent in males and can present with extranodal involvement (lung, skin and marrow infiltration) and haemophagocytic lymphohistocytosis. The long‐term overall survival is approximately 70–90% in children and over 70% in adults. Staging systems and prognostic risk factors are different in both childhood and adult ALCL. Treatment in adults is typically anthracycline‐based, with autologous stem cell transplantation (ASCT) salvaging patients in relapsed disease. There is evidence for ALL‐like therapy or intensive, pulsed anthracycline‐based induction in children. ASCT, allogeneic SCT and vinblastine maintenance are all considered reasonable options in relapsed childhood disease. The anti‐CD30 immunoconjugate Brentuximab Vedotin and the specific ALK inhibitor Crizotinib are changing the treatment paradigm in ALCL (ALK‐positive or negative) and ALK‐positive ALCL respectively. Both agents have shown encouraging responses in relapsed ALCL. It remains to be seen how these novel agents are used, but it is very possible that they may improve overall responses and survival in both children and adults. This review highlights the presentation, histopathological features, prognostic factors, and evidence‐based treatment approaches in the first line and relapsed setting in ALK‐positive ALCL. The review concludes by discussing the novel approaches using Brentuximab and Crizotinib which are being tested in clinical trials.